1996
DOI: 10.3181/00379727-213-44049
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Decreases Mean Blood Pressure and Selectively Increases Regional Blood Flow in Normal Rats

Abstract: The insulin-like growth factor-I (IGF-I) and its receptors are widely distributed in peripheral vascular tissue, yet their role in the regulation of blood pressure and blood flow remains unknown. This study investigated the effect of IGF-I on blood pressure and selected regional blood flow in normal Wistar rats anesthetized with chloralose/urethane. The femoral artery was cannulated and used to monitor arterial blood pressure. Electromagnetic flow probes were placed around the left common iliac artery, left re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The cardioprotective effects of GH may have been mediated by an elevation of plasma IGF-I levels. In fact, it has been shown that IGF-I stimulates nitric oxide (NO) release from cultured endothelial cells, and NO is an important regulator of vascular function (37). In contrast, hexarelin did not stimulate plasma levels of IGF-I.…”
Section: Discussionmentioning
confidence: 98%
“…The cardioprotective effects of GH may have been mediated by an elevation of plasma IGF-I levels. In fact, it has been shown that IGF-I stimulates nitric oxide (NO) release from cultured endothelial cells, and NO is an important regulator of vascular function (37). In contrast, hexarelin did not stimulate plasma levels of IGF-I.…”
Section: Discussionmentioning
confidence: 98%
“…Short-term injection of IGF-1 decreased mean arterial pressure, and this effect was inhibited by preinfusion of an NO inhibitor, indicating that the decrease in blood pressure in response to IGF-1 is mediated by NO. 138 A significant elevation of arterial pressure was also observed in mice homozygous for a site-specific insertional mutation in exon 3 of IGF-1. 139 Peripheral resistance and systolic blood pressure were increased in liver-specific IGF-1 knockout mice.…”
Section: Hypertensionmentioning
confidence: 97%
“…Moreover, there is an increasing body of evidence demonstrating that IGF-I exerts multiple vascular effects through endocrine, autocrine, and paracrine mechanisms (3). Because IGF-I induces NO production in endothelial cells, it is a potent mediator of vasodilation (38) and is capable of lowering systemic blood pressure (30). IGF binding protein 1 (IGFBP1) is a carrier protein that binds to IGF-I with high affinity and therefore is placed in a critical regulatory position between IGF-I and its receptor.…”
Section: Discussionmentioning
confidence: 99%